PENYELESAIAN SENGKETA PERBANKAN SYARIAH DALAM PERSPEKTIF HUKUM PROGRESIF - Dewi Nurul Musjtari (Fakultas Hukum Universitas Muhammadiyah Yogyakarta, 2013)
The purpose of this study was to explain Islamic banking dispute serrlement in progressive legal perspective relevant to thinking about law Hans Kelsen for the development of progressive legal concept that in order to complement and enhance the operation of law in society.The paradigm of this research is constuktivisme, while the method of research was carried out by two strategies, namely the research literature (library research) and case studies (case study). Literature study conducted on all documents or literature on legal theory. Documents then grouped according to the dimension of time or periodization. Case studies conducted in this study is a case related to the operation of law in society related to Islamic banking dispute resolution. This study used a socio-legal rules governing this studies. This research using secondary data and primary data. Secondary data was obtained through the Research Library (Library Research) and Legal Document. Secondary data include: 1) Primary Legal Materials, in the form of Article 55 of Law No. 21 Th 2008 and explanations, Article 39 of Law No. 30 Th, 1999, Law No. 4 Th. 1996, Law No. 50 Th. 2009 àStatute aproach civil relationship à Theory Agreement and Procedural Law, Procedural Law Religious Court, the Constitutional Court Decision No. 93 / PUU-X / 2012 à Pollitik àTeori Political Law Law, Religion and ruling Justice Court Judge District Court relating to Settlement Dispute Guarantee Mortgage. 2) Secondary Legal Materials, consisting of a book-nail on legal theory, legal philosophy, paradigm, socio-legal studies and research methods. Primary data was obtained through research in the field (Field Research) was done by observation, interview, which includes: 1) Law sanction institution: Judges. 2) Role Occupant: Judges, Academics, Advocate, Legal Staff of The Islamic Bank, Islamic Bank Customer, Successor (cadre) Satjipto Rahardjo and Hans Kelsen. à implemantation with hermeneutics and phenomenology. Keywords: Dispute Settlement, Islamic Banking, Progressive Legal Perspective